The effects of child anxiety and depression on concordance between parent‐proxy and self‐reported health‐related quality of life for pediatric liver transplant patients. (9th July 2021) - Grant, Amy; Ng, Vicky L.; Nicholas, David; Dhawan, Anil; Yazigi, Nada; Ee, Looi C.; Stormon, Michael O.; Gilmour, Susan M.; Schreiber, Richard A.; Carmody, Erin; Otley, Anthony R.
Abstract: Background: HRQOL is a key outcome following pediatric LT. Parent‐proxy reports may substitute for patients unable to report their own HRQOL. This study compared parent‐proxy and self‐reported HRQOL in children who have undergone LT. Methods: Pediatric LT recipients between the ages of 8 and 18 years, and a parent, completed self and proxy versions of the PeLTQL questionnaire, PedsQL Generic and Transplant modules, and standardized measures of depression and anxiety. Results: Data from 129 parent–patient dyads were included. Median parent age was 44 years, and most (89%) were mothers. Median patient age was 2.5 years at LT and 13.6 years at the time of study participation. Parents had significantly lower scores than patients on PedsQL total generic (70.8 ± 18.5 and 74.3 ± 19.0, p  = .01), PeLTQL coping and adjustment (63.0 ± 15.6 and 67.3 ± 16.2, p  < .01), and social‐emotional (66.3 ± 14.9 and 71.9 ± 15.6, p  < .001) domains. Higher patient anxiety and depression were related to larger absolute differences between parent‐proxy and self‐reported scores on all HRQOL measures (all p  < .05). In this disparity, parents reported higher HRQOL scores than their child as self‐reported anxiety and depression scores increased. Conclusions: Differences in concordance between parent‐proxy and self‐reported HRQOL scores can be more prominent when children have more symptoms of anxiety and depression. Children's mental health symptoms should be queried, if feasible, when interpreting differences in parent and child reports of HRQOL.